2008
DOI: 10.1002/pbc.21777
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node biopsy in pediatric soft tissue sarcomas of extremities

Abstract: BackgroundSentinel Node Biopsy is an established staging technique in many adult malignancies. However, only few reports describe this procedure for the evaluation of regional lymph nodes in childhood and adolescents. Our experience with sentinel node biopsy in soft tissue sarcomas of extremities in children is reported.MethodsSeventeen children were evaluated with sentinel node biopsy between 2002 and 2007: 11 at initial surgery, 5 at primary re‐excision, 1 at local relapse. The diagnosis was rhabdomyosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…They also found the SN metastasis in one RMS patient out of six cases (16.7%) who underwent lymphoscintigraphy/SLNB whereas no SN metastasis was observed in patients with non‐RMS sarcomas (0/17) . Those findings were consistent with results from previous reports with 11.1–33.3% SN positivity rate for RMS patients …”
Section: Discussionsupporting
confidence: 89%
“…They also found the SN metastasis in one RMS patient out of six cases (16.7%) who underwent lymphoscintigraphy/SLNB whereas no SN metastasis was observed in patients with non‐RMS sarcomas (0/17) . Those findings were consistent with results from previous reports with 11.1–33.3% SN positivity rate for RMS patients …”
Section: Discussionsupporting
confidence: 89%
“…In a recent review of SLNB in 9 pediatric patients with RMS, a positive SN was found in 1 patient who received regional lymph node irradiation but died 40 months later due to systemic recurrence[6]. De Corti reviewed 5 children with RMS of the extremities who underwent lymphoscintigraphy and SLNB and found SN metastasis in one patient with an alveolar histology[5]. In our study, the SN positivity rate for RMS patients was 16.7% (1/6), similar to the rate seen in IRS-IV[21].…”
Section: Discussionmentioning
confidence: 99%
“…These limitations of physical exam and imaging have sparked the use of SNB as a way to ensure that the most clinically relevant lymph nodes are being sampled. This procedure is routinely used in adults with breast cancer and melanoma 13, and experience is growing in children 6–10. Pediatric studies have most commonly used SNB for evaluation of extremity soft tissue sarcoma, where some type of lymph node sampling is often mandatory even when no clinically suspicious nodes are present 2.…”
Section: Discussionmentioning
confidence: 99%
“…This technique therefore helps surgeons sample the most clinically relevant nodes, instead of performing either random sampling or more extensive and often debilitating dissections. Use of SNB has most commonly been utilized in RMS of the extremities 6–10. We now describe the first known use of SNB in parameningeal RMS.…”
Section: Introductionmentioning
confidence: 99%